2015
DOI: 10.1053/j.seminoncol.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

MEK1/2 Inhibitors: Molecular Activity and Resistance Mechanisms

Abstract: Aberrant activation of the three-layered protein kinase cascade, Raf/MEK/ERK, is often detected in human cancer, which is mainly attributed to the oncogenic alterations of RAF, or its upstream activators RAS or cell surface receptor tyrosine kinases. Deregulated activity of the Raf/MEK/ERK pathway drives uncontrolled tumor cell proliferation and survival, thus providing a rational therapeutic target for the treatment of many cancers. While Raf, MEK1/2, and ERK1/2 are equally important targets for the design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 113 publications
3
91
0
Order By: Relevance
“…Numerous reports have shown the aberrant activation of Raf/MEK/ERK pathway in variety of human cancers [36, 37]. Recent studies also demonstrated aberrant regulation of this pathway was associated with cancer chemoresistance [14, 15]. In the present study, we observed that miR-939 overerxpression in GC cells significantly decreased MEK1/2 phosphorylation and Raf-1 level, while restoration of SLC34A2 rescued these effects.…”
Section: Discussionsupporting
confidence: 67%
“…Numerous reports have shown the aberrant activation of Raf/MEK/ERK pathway in variety of human cancers [36, 37]. Recent studies also demonstrated aberrant regulation of this pathway was associated with cancer chemoresistance [14, 15]. In the present study, we observed that miR-939 overerxpression in GC cells significantly decreased MEK1/2 phosphorylation and Raf-1 level, while restoration of SLC34A2 rescued these effects.…”
Section: Discussionsupporting
confidence: 67%
“…While, on one hand, this observation indicates that just one of them can be enough to dysregulate the entire Ras/Raf/MEK/ERK1/2 cascade, on the other hand it further supports the critical role played by the abnormal activation of this cascade in carcinogenesis. As analyzed in detail in a recent review by Wu and Park [22], RAS mutations are detected in more than half of the pancreas cancers, and in about a third of colon, biliary tract, and skin cancers, as well as in around a fifth of small intestine or lung cancers. A series of other cancers (ovary, salivary glands, urinary tract, cervix, endometrium, upper aero-digestive tract, prostate, thyroid, and hemopoietic/lymphoid cells) [22] are characterized by RAS mutations, although with slightly lower proportions (ranging from 14% to 18%).…”
Section: Erk1/2 As An Emerging Target In Anti-cancer Therapymentioning
confidence: 99%
“…As analyzed in detail in a recent review by Wu and Park [22], RAS mutations are detected in more than half of the pancreas cancers, and in about a third of colon, biliary tract, and skin cancers, as well as in around a fifth of small intestine or lung cancers. A series of other cancers (ovary, salivary glands, urinary tract, cervix, endometrium, upper aero-digestive tract, prostate, thyroid, and hemopoietic/lymphoid cells) [22] are characterized by RAS mutations, although with slightly lower proportions (ranging from 14% to 18%). Also, mutations in BRAF, particularly those involving the Valine600 codon, are found at very high percentages in several cancers.…”
Section: Erk1/2 As An Emerging Target In Anti-cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant activation of the Raf/MEK/ERK, which drives uncontrolled tumour cell proliferation and survival, is detected in a variety of human cancers [47][48][49][50]. Cell surface receptor tyrosine kinases, or oncogenic alterations of RAF, or its upstream activators RAS, contribute to aberrant activation of this pathway [51][52][53][54]. DUSP4, a dual-specificity phosphatase, can inactivate Raf/MEK/ERK signalling pathway through dephosphorylating p-ERK.…”
Section: Discussionmentioning
confidence: 99%